2023
DOI: 10.1101/2023.01.13.23284467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coverage of primary and booster vaccination against COVID-19 by socioeconomic level: A nationwide cross-sectional registry study

Abstract: High and equitable COVID-19 vaccination coverage is important for pandemic control and prevention of health inequity. However, little is known about socioeconomic correlates of booster vaccination coverage. In this cross-sectional study of all Norwegian adults in the national vaccination program (N = 4,190,655), we use individual-level registry data to examine coverage by levels of household income and education of primary (≥2 doses) and booster (≥3 doses) vaccination against COVID-19. We stratify the analyses… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Bennett et al and Della Polla et al reported on the possible effect of previous COVID-19 infection on first and second booster intention respectively, based on self-reported surveys with limited study samples, but the results were not significant [9,10]. A study by Hansen et al showed a significant negative effect of COVID-19 infection on first booster uptake [11], which is in line with our study results.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Bennett et al and Della Polla et al reported on the possible effect of previous COVID-19 infection on first and second booster intention respectively, based on self-reported surveys with limited study samples, but the results were not significant [9,10]. A study by Hansen et al showed a significant negative effect of COVID-19 infection on first booster uptake [11], which is in line with our study results.…”
Section: Discussionsupporting
confidence: 90%
“…Studies investigating booster willingness showed as well conflicting results concerning sex [5][6][7]. Regional differences in booster uptake could possibly be explained partially by socioeconomic factors and migration background which can influence vaccine hesitancy [2,8,9,11,12]. The Belgian regional effect was also demonstrated by a previous study concerning PC uptake in Belgium [13].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations